(untitled) (Patan Pragya, 2022)
Ethnic identity is a concept that is based on the feeling of the community, cultural heritage, traditional values and beliefs, ritual practices, mother tongue, specific geographical territory, and religion and can be measured by using different techniques and methods. Anthropologists and identity specialists developed various methods for the measurement of ethnic identity. This research examined the newly developed ethnic identity measures of the Ethnic Identity Scale (EIS),the Multi-group Ethnic Identity Measure (MEIM), and the revised (MEIM-R) from anthropological perspectives. Exploration, commitment, and affiliation are the major factors for the measurement of identity and this article has used these factors. Data gathered from the field of Bankariya habitats in Dhading district were analyzed for identity measurement. For the calculation of Bankariya’s identity, only 65 respondents out of 79 were selected. Most of them have identity feelings and pride in their ethnic group. More than 90 percent of Bankariya people have actively participated in their cultural practices but only 3 percent of people are active in ethnic organizations. The research also explores the demographic and geographic features of the Bankariya people, the theoretical framework of identity, and measuring techniques.